Essential Role of the Iron-Regulated Outer Membrane Receptor FauA in Alcaligin Siderophore-Mediated Iron Uptake in Bordetella Species - Brickman, Timothy J.; Armstrong, Sandra K. (East Carolina University, 1999)
Phenotypic analysis using heterologous host systems localized putative Bordetella pertussis ferric alcaligin transport genes and Fur-binding sequences to a 3.8-kb genetic region downstream from the alcR regulator gene. Nucleotide sequencing identified a TonB-dependent receptor family homolog gene, fauA, predicted to encode a polypeptide with high amino acid sequence similarity with known bacterial ferric siderophore receptors. In Escherichia coli, the fauA genes of both B. pertussis and Bordetella bronchiseptica directed the production of a 79-kDa polypeptide, approximating the predicted size of the mature FauA protein. B. bronchiseptica fauA insertion mutant BRM17 was unable to utilize ferric alcaligin, and in complementation analyses ferric alcaligin utilization was restored to this mutant by supplying the wild-type fauA gene in trans. Mutant BRM18, carrying a nonpolar in-frame fauA deletion mutation, was defective in ferric alcaligin utilization and 55Fe-ferric alcaligin uptake and no longer produced a 79-kDa iron-regulated outer membrane protein. In complementation analyses, BRM18 merodiploids bearing the wild-type fauA gene in trans regained ferric alcaligin siderophore transport and utilization functions and produced the 79-kDa protein. Analysis of a plasmid-borne fauA-lacZ operon fusion confirmed that fauA is subject to iron regulation at the transcriptional level and that cis-acting transcriptional control elements mediating fauA iron repressibility reside within the 3.8-kb PstI fauA DNA region. Moreover, expression of the fauA-lacZ fusion gene under iron starvation conditions was shown to be alcR dependent. FauA is a 79-kDa iron-regulated outer membrane receptor protein required for transport and utilization of ferric alcaligin siderophore complexes by Bordetella species. Originally published Journal of Bacteriology, Vol. 181, No. 19, Oct 1999
Keywords: Bordetella pertussis; Ferric alcaligin; FauA receptor